Pembuatan Bioetanol Dari Nira Nipah Dengan Penambahan Tween 80 Dan Ergosterol Pada Proses Fermentasi Menggunakan Sacharomyces Cereviceae - Mohammad Rezky; Chairul Chairul; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Nypah  sap is one of potential materials  it’s  processed into bioethanol. Availability of nypah palm land in Indonesia and a fairly high sugar content (15-20%) makes nipa sap has the potential  it’s processed into bioethanol. Ergosterol is an essetial component of yeast cells that maintains the integrity of the membrane. It’s  invetigated as an important factor the ethanol tolerance of yeast cells. Ethanol and hypoxia were found to have negative and synergistic effects on the total ergosterol contents of both strains and  it’s  significantly reduce the free ergosterol. Effect of a surfactant Tween 80 on the bacterial for growth, increase the glucose consumption rate at the later stage of the fermentation, maintain the intact structure of  yeast S. Cereviceae.  Preparation  started  by the  yeast S. Cereviceae inoculum in the 10% of fermentation medium so that yeast an  able to  adapt and ready for fermentation.  Fermentation  place  taked in batches with  volume of 2  liters  of fermentation medium, variations in the tween 80 and ergosterol and variations of fermentation at time 24, 36, 48, 60 dan 72 hours and then concentration of yeast 4 g/l. The stirring speed in 200 rpm and  temperature of fermentation at room temperature (25-300 C)it’s  selected conditions. Bioethanol concentrations has been analyzed by used  gas kromatografi. The process of fermentation optimum conditions indicated in the addition of tween 80 10 ml and ergosterol 1 gram    at the time of 72  hours having the initial sugar concentration of 161,81  mg/ml. concentration Bioethanol obtained in this condition at 20,47% (v/v). Keywords: Ergosterol, Nipa sap, Saccharomyces cerevisiae, Tween 80.